The Effects of Representatives' Power within their own Organizations on the outcome of a Negotiation - Jackson, Conrad N.; King, Donald C. (Academy of Management Journal, 1983)
The article examines the impact of representatives' power within their own organization on the outcome of a negotiation and the dynamics of interorganizational relationships. The authors begin by discussing various studies that have been done and explains the focus of each. They believe that a high-power boundary-spanning person (BSP) (a person who links one organization to another) will complete negotiations in less time with fewer deadlocks, get more resources exchanged, and achieve greater productivity and greater satisfaction. To test this theory, they used 120 undergraduate students. They found that negotiation time was affected by interorganizational power of BSPs.